Changes Of Some Chemical Properties Of Soil After Rice Production The Impact Of Giving Cow Manure - Salawati Salawati; Sjarifuddin Ende; Lukman Lukman (University of Prof. Dr. Hazairin, SH, 2022)
Rice plants are able to express their genetic abilities if their growth is supported by an optimal growing environment such as both organik and inorganik fertilization. The ability to plan nutrients to support the growth of rice plants has decreased and is less responsive to fertilization, N, P, K. because the level of soil fertility decreases, the period of biological fertility in the period of physical fertility and paddy soil. This study aims to determine the changes in some chemical properties of the soil after the first rice harvest, using cow manure and biochar and N, P, K, Zn fertilizers as basic fertilizers, using a randomized block design with 7 levels of cow manure treatment that is, 0, 2.5, 5, 7.5, 10, 12, 5 and 15 tons ha-1. Collected data were analyzed using variance and advanced test DMRT 5% level. The results showed that there was a change in some chemical properties of the rice field soil after harvesting the Mekongga variety, among others, a decrease in pH to 1 level, an increase in Organik C 95.41%, N total 80%, K Total 56.49%, CEC, 63.57%. Zn is available 46.55% and P is available 422.52%.